"توضيح الأحكام على تحفة الحكام" للشيخ عثمان بن بالقاسم ابن المكي التوزري الزبيدي المتوفى (1350ه): تحقيق ودراسة - ميشات، آمنة محمد نويجي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The dissertation revolves around Sheikh Othman b. al-Makki b. Belgacem al-Tuzuri (1266/,1849CE-1350/1931CE), and his manuscript Tawdih al-Ahkam fi Tuhfat al-Hukkam in which he commented on Ibn 'Asim al-Andalusi's didactic poem (urjuzah) entitled Tuhfat al-Hukkam fi Nukat al-'Uqud wa al-Ahkam. The researcher has made a critical editing and study of this manuscript as the subject of her dissertation for two main reasons. The first reason concerns the intrinsic scholarly and intellectual value of the manuscript as well as it being a commentary on one of the most important works in applied jurisprudence. The second reason pertains to the standing of its author among Maliki jurists in the modern age in general and in Tunisia in particular. In addition to the research proposal, the dissertation is made of two parts: an analytical constructive part and a critical and documental one. The first part has been prefaced by a brief introduction on Ibn 'Asim al-Andalusi, the author of the didactic verse, al-Tuhfah. This introduction includes an account of Ibn Asim's biography and an exposition on the significance of his Tuhfat al-Hukkam in Maliki jurisprudence and the commentary written on it. The researcher then moved to discuss Sheikh al-Tuzuri, the author of the commentary. She provides an historical exposition and analysis of the political, social, economic, academic and cultural conditions of the general Tunisian milieu in which al-Tuzuri lived. She also devotes her attention to providing a biographical description of the Sheikh's personality of the Sheikh, and to identifying and introducing his teachers and students, as well as to describing his scholarly legacy including both his published works and those in manuscript form. In order to bring into prominence the scholarly value of the manuscript under examination, the researcher undertook a detailed study of the methodology al-Tuzuri followed in his commentary on the above-mentioned didactic verse: she expounded his style of presentation of the scientific material relevant to the topics in question; she also shed light on the principles of Ijtihad on which he based his juristic preferences and decisions as well as on his approach in discussing disputed issues and the grounds on which he set out to give preference to certain juristic views over others. The second part of the dissertation consists of the critically edited text of the manuscript which is the researcher has confined herself to the first and second volumes. In this respect, she followed the methodological and technical rules established by expert scholars in the field, thus laboring to fixing the text as accurately as possible and presenting it free from error and distortion. She also did her best to document al-Tuzuri's citations and identify his sources. Among the important findings arrived at in the present work are the following: 1. Bringing to the fore the prominent place al-Tuzuri occupies in the scholarly life and reformist movement of Tunisia during the second half of the nineteenth century and first third of the twentieth; 2. Shaking the dust off his valuable commentary on Ibn 'AÎim's didactic poem which reflects his creative interaction with the realities of his milieu and issues of his time.